Estimating and monitoring oil palm productivity using remote sensing / Nora Dhalina Ab. Manaf - Ab. Manaf, Nora Dhalina (2013)
This study was regarding the application of remote sensing for monitoring and estimating oil palm productivity. The study consist of three main objectives that is to develop a basic method to estimate and monitoring oil palm productivity using remote sensing, to classify the area of oil palm plantation based on their productivity using Normalized Difference Vegetative Index (NDVT) and to assess the accuracy of remote sensing product. In this project, 3 years of SPOT 5 satellite image have been used to detect the changes of oil palm estate. So, it can be used to identify the location and productivity of oil palm. This will make easier for monitoring oil palm productivity. Finally, the maps show productivity of oil palm for 2005, 2006 and 2007 will be produced.